The Condition of Internal Quality Assurance Implementation in Opportunity Expansion Schools under Uttaradit Primary Education Ser-vice Area Office 1 - Doungpootim, Laddawan; Natun, Jaruwan (MCU Haripunchai Review, 2025)
The purposes of this research were to study the internal education quality assurance of opportunity expansion schools under Uttaradit Primary Education Service Area Office 1. The population consists of administrators, teachers, and educational personnel in opportunity expansion schools, totaling 778 individuals. The sample group comprises 260 individuals, determined using Krejcie and Morgan’s sample size table. This includes 36 administrators selected through purposive sampling and 224 teachers and educational personnel chosen using stratified and simple random sampling methods.The research instrument used this research was 5 rating scale questionnaires, consisting of 33 items.The item-total correlation ranged from .80 – 1.00, and the reliability coefficient was .985. The statistical tools used for data analysis were percent, mean and standard variation. The research findings revealed that The internal education quality assurance of opportunity expansion schools under Uttaradit Primary Education Service Area Office 1 overall, the average is at the highest level, and when considering respect, the highest average is setting the educational development plans for school in accordance with the educational standards. The second is the monitor performance to develop educational institutions to have quality according to educational standards, and the lowest average is setting for educational standards.